Językowy obraz rzeczywistości we współczesnej stołecznej prasie - Koriakowcewa, Jelena (Przegląd Rusycystyczny, 2006)
JĘZYKOWY OBRAZ RZECZYWISTOŚCI ROSYJSKIEJ WE WSPÓŁCZESNEJ STOŁECZNEJ PRASIE S t r e s z c z e n i e Autorka objęła obserwacją artykuły publicystyczne dotyczące rosyjskiego życia społecznego, aby ustalić, jak jest oceniana przez stołecznych dziennikarzy jego jakość. Skupiła się na kilku wybranych szczególnie opiniotwórczych gazetach. Zbadała środki językowe, w których przejawiła się agresja i dezaprobata oraz nastawienie dziennikarzy na manipulowanie opinią publiczną. THE LINGUISTIC IMAGE OF RUSSIAN LIFE IN THE CONTEMPORARY MOSCOW PRESS S u m m a r y The focus of the article is the analysis of the linguistic image of Russian society created by journalists of the Moscow infl uential newspapers. The analysis covers more recent pejorative derivatives and idioms found in the Moscow press that have emerged the past year and have not yet been listed in professional dictionaries. The autor perceive the communicative intentions of journalists and their methods of evaluation of concepts Nation, Citizen, Patriotism, State, Peace. The modern publicistic texts are characterized by continually growing trend to intensify negative emotions. Besides expressive words have also manipulate function.